Determination of ionic calcium in frog skeletal muscle fibers. - López, J R (1983)
Ionic calcium concentrations were measured in frog skeletal muscle fibers using Ca-selective microelectrodes. In fibers with resting membrane potentials more negative than -85 mV, the mean pCa value was 6.94 (0.12 microM). In fibers depolarized to -73 mV with 10-mM K the mean pCa was 6.43 (0.37 microM). This increase in the intracellular [Ca2+] could be related to the higher oxygen consumption and heat production (Solandt effect) reported to occur under these conditions. Caffeine, 3 mM, also produced an increase in the free ionic calcium to a pCa of 6.52 (0.31 microM) without changes in the membrane potential. Lower caffeine concentrations, 1 and 2 mM, did not change the fiber pCa. Lower Ca concentrations in the external medium effectively reduced the internal ionic calcium to an estimated pCa of 7.43 (0.03 microM).